The origin and development of compliance regulations (Economic and Political Thought, 2020)
The huge rise in legal and non-legal regulations and the creation of new law enforcement institutions increase the risk of non-compliance to entities participating in business transactions. Enterprises, wanting to avoid the consequencesof non-compliance with applicable regulations, implement compliance norms aimed at minimizing the risk of its occurrence. Until recently, the phenomenon concerned only the largest enterprises operating in specific industries. Currently, compliance norms are becoming more and more popular in small and medium enterprises, as well as are a strategic factor forthe development and increase in competitiveness. Having the above in mind, the article aims to present the origin and circumstances of the development of compliance regulations. The hypothesis that compliance genesis shouldbe traced in the United States at the turn of the century is adopted and discussed. Then, the events that had a key impact on the development of compliance norms are cited, i.e. the Watergate scandal and the investigation of the Securities and Exchange Commission, the abuse of public procurement in the US arms industry in the eighties, the appointment of the NationalCommission for Fraud in Financial Reporting and the creation of a Committeeof Sponsoring Organizations of the Treadway Commission, Ronald Reagan’s criminal law reform, the work of the Organization for Economic Cooperation and Development to combat corruption, and corporate scandals of the early 2000s (Enron, WorldCom).
Keywords: compliance, compliance norms, first compliance norms, genesis of compliance norms, compliance risk